RETRACTED: Moxibustion Modulates Sympathoexcitatory Cardiovascular Reflex Responses Through Paraventricular Nucleus - Cheng, Ling; Li, Peng; Patel, Yash; Gong, Yiwei; Guo, Zhi-Ling; Wu, Huangan; Malik, Shaista; Tjen-A-Looi, Stephanie C. (Frontiers in Neuroscience, 2019)
Electroacupuncture (EA) point specific (ST36-37) stimulation decreases cardiovascular reflex responses through supraspinal regions such as the hypothalamic paraventricular nucleus (PVN) while mechanical stimulation of acupoints decreases pressor responses through peripheral thermal transient receptor potential vanilloid type-1 (TRPV1). Moxibustion generating heat applied at acupoint in combination with antihypertensive drugs decreases elevated blood pressure. We hypothesized that moxibustion modulates sympathoexcitatory cardiovascular responses through the hypothalamic PVN and peripheral heat sensitive TRPV1 in the absence of antihypertensive drugs. Rats were anesthetized, ventilated, and heart rate and mean blood pressure were monitored. Gastric distention induced consistent pressor reflex responses every 10-min. Thirty-min of bilateral moxibustion at acupoint ST36, overlying the deep peroneal nerves, reduced the gastric distention evoked elevation in blood pressure. Blood pressure reflex responses were not reduced by both EA and moxibustion at G39. The moxibustion inhibition but not EA inhibition of the cardiovascular responses was reversed with blockade of local heat sensitive TRPV1 at ST36. Accordingly, activation of thermal TRPV1 by moxibustion at an average of 44.2 °C in contrast to 40°C reduced the pressor responses. Naloxone, an opioid receptor antagonist, microinjected into PVN inhibited transiently the effect of moxibustion. Thus, activation of peripheral heat sensitive TRPV1 mediated the moxibustion-inhibition, but not EA-inhibition, of sympathoexcitatory cardiovascular reflex responses through hypothalamic PVN opioid system.